2009
DOI: 10.1519/jsc.0b013e3181a2d7b3
|View full text |Cite
|
Sign up to set email alerts
|

Power Variables and Bilateral Force Differences During Unloaded and Loaded Squat Jumps in High Performance Alpine Ski Racers

Abstract: The purpose of this paper was to investigate the power-load relationship and to compare power variables and bilateral force imbalances between sexes with squat jumps. Twenty men and 17 women, all members of the Austrian alpine ski team (junior and European Cup), performed unloaded and loaded (barbell loads equal to 25, 50, 75, and 100% body weight [BW]) squat jumps with free weights using a specially designed spotting system. Ground reaction force records from 2 force platforms were used to calculate relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 14 publications
2
30
1
1
Order By: Relevance
“…In different performance tests for maximal strength and muscle elasticity, females have reached 54-82% of the values obtained by males [1,3,4,5,6]. As reported by Patterson et al [7], men displayed significantly higher values for relative average power and jump height in squat jump (SJ) than women. A statistically significant gender difference was found in SJ and countermovement jump (CMJ) (25% and 19% respectively) in Bosco et al [8] study.…”
Section: Introductionmentioning
confidence: 82%
“…In different performance tests for maximal strength and muscle elasticity, females have reached 54-82% of the values obtained by males [1,3,4,5,6]. As reported by Patterson et al [7], men displayed significantly higher values for relative average power and jump height in squat jump (SJ) than women. A statistically significant gender difference was found in SJ and countermovement jump (CMJ) (25% and 19% respectively) in Bosco et al [8] study.…”
Section: Introductionmentioning
confidence: 82%
“…As indicated by Bosco et al (2002) there was a statistically significant gender difference in CMJ and SJ (19% and 25%,respectively). Patterson et al (2009) concluded that male displayed significantly higher values for relative average power and jump height in SJ than female. Buśko and Gajewski (2011) reported that the male subjects had much better performance than the female subjects of comparable physical conditions did.…”
Section: Discussionmentioning
confidence: 99%
“…Насупрот утиску да је алпско скијање дина-мична активности са пуно експлозивних покре-та, угаоне брзине у зглобу колена и кука показују да скијање није спорт који карактерише макси-мална брзина покрета (Berg, Eiken, & Tesch, 1995;Patterson, Raschner, & Platzer, 2009). Просечне угаоне брзине у зглобу колена се крећу у распону 20-40º/s, а максималне забележене, од 69º/s, су да-леко од угаоних брзина у зглобу колена спринтера и скакача (1000º/s) или бициклиста (200-400º/s) (Berg & Eiken 1999).…”
Section: карактеристике мишићне активности ногу код скијашаunclassified